Mesenchymal stem cells combined with barrier domes enhance vertical bone formation. (19th December 2012) - Zigdon‐Giladi, Hadar; Lewinson, Dina; Bick, Tova; Machtei, Eli E.
Abstract Aim To enhance vertical bone formation in a rat calvarium following combination of guided bone regeneration (GBR) and transplantation of bone marrow derived mesenchymal stem cells (bmMSC). Materials and Methods Gold domes (7 mm radius, 5 mm height) were filled with 5 × 105 bmMSC or osteogenic transformed bmMSC (otMSC) that were isolated from tibia of inbred rats and mixed with βTCP. Domes filled with βTCP served as control. Rats were sacrificed after 3 months. New bone formation was analysed by histology and histomorphometry. Results In all rats hard tissue filled the space under the dome. In the lower part of the specimens the newly formed mature bone was continuous with the original calvaria, whereas the upper (distal) part of the augmented tissue contained residual scaffold surrounded by connective tissue. Histomorphometric analysis revealed that cell transplantation doubled vertical bone height: (bmMSC 4.13 ± 0.5 mm, otMSC 4.14 ± 0.3 mm βTCP 2.29 ± 0.22 mm, p ≤ 0.001). Bone area fraction (%) was significantly increased following transplantation of otMSC (47.2 ± 2.5%) when compared with bmMSC (37.3 ± 3.35%) and with βTCP (31.09 ± 2.7%) (p ≤ 0.031 versus bmMSC, p ≤ 0.0004 versus control) Conclusion In a rat calvaria model transplantation of both otMSC and bmMSC, when combined with GBR significantly enhanced bone formation.